2021
DOI: 10.1515/res-2021-0014
|View full text |Cite
|
Sign up to set email alerts
|

Using a Multi-Methods Approach to Investigate Disaster Preparedness of Community Libraries in the North West Province of South Africa

Abstract: Disasters can occur anywhere, and no organisation is immune to disasters. Community libraries in South Africa have experienced disasters over the past years, ranging from natural disasters to human-made disasters. This research aims to investigate the disaster preparedness of community libraries in the North West Province of South Africa. A multi-methods approach that involved questionnaires, interviews, and document analysis was used. The study results revealed that although community libraries have experienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…For instance, Ayoung et al (2016) found that libraries in Ghana are ill-equipped to withstand and avert disasters. Similarly, community libraries in South Africa’s North West Province seldom prioritize disaster preparedness, with librarians mistakenly believing that libraries are immune to disasters and that disaster preparedness is not their responsibility (Chizwina and Ngulube, 2021). Likewise, a disaster management plan is also absent among the majority of academic libraries in south-eastern Nigeria (Chiderah and Iroeze, 2021) and Sri Lanka (Wijayasundara, 2021).…”
Section: Review Of Related Literaturementioning
confidence: 99%
“…For instance, Ayoung et al (2016) found that libraries in Ghana are ill-equipped to withstand and avert disasters. Similarly, community libraries in South Africa’s North West Province seldom prioritize disaster preparedness, with librarians mistakenly believing that libraries are immune to disasters and that disaster preparedness is not their responsibility (Chizwina and Ngulube, 2021). Likewise, a disaster management plan is also absent among the majority of academic libraries in south-eastern Nigeria (Chiderah and Iroeze, 2021) and Sri Lanka (Wijayasundara, 2021).…”
Section: Review Of Related Literaturementioning
confidence: 99%